Low Carbohydrate Diets in Men with Prostate Cancer May Reduce Risk of Cardiovascular Disease. (29th May 2020) - Lin, Pao-Hwa; Howard, Lauren; Ngo, Alexis; Ramirez-Torres, Adela; Cheng, Susan; Mack, Alexandra; Freedland, Stephen
Abstract: Objectives: Both weight loss and low-carbohydrate diets (LCDs) have been shown to slow prostate cancer (PC) growth in animal models. Given the significant weight loss and purported metabolic benefits of LCDs to lower insulin and glucose (two key cancer growth factors), there is growing interest in using them in cancer patients. However, critics point to potentially increased cardiovascular disease (CVD) as a major risk. The objective of this study is to examine the effect of an LCD on estimated CVD risk within the context of randomized trials of LCD in PC patients. Methods: Carbohydrate and Prostate Cancer (CAPS) 1 and CAPS2 studies were randomized clinical trials testing 6 mo. of an LCD vs. control (asked to make no diet changes) in overweight PC patients. CAPS1 included 34 men starting androgen deprivation therapy (ADT) and tested whether LCD prevents insulin resistance. CAPS2 included 45 men with recurrent PC after primary treatment and tested whether LCD slows PC growth. Primary results have been presented. In this post-hoc analysis, we calculated 10-year risk of CVD at baseline, 3 mo., and 6 mo. in each study based on a CVD risk model developed from the Framingham Heart Study. This score accounts for age, diabetes, smoking, treated and untreated systolic blood pressure and BMI. Comparisons between arms were made using t-tests. A mixed model was used to test longitudinal changes in CVD risk combining data from both studies but adjusting for study. Results: In CAPS1, the 10-year estimated CVD risk was unchanged from baseline to 6 mo. at 29% in controls but decreased from 31% to 23% in the LCD arm (p = 0.23). In CAPS2, CVD risk increased from 34% to 35% in controls but decreased from 32% to 28% in the LCD arm (p = 0.005). When data from the two studies were combined, the LCD was associated with a lower 10-year estimated CVD risk vs. control over the study period (p < 0.001). Conclusions: Across two prospective randomized trials, an LCD in men with PC was associated with a lower estimated 10-year risk of CVD than control patients making no diet changes. These data support the safety of LCDs for men with PC. Given CVD is the number one cause of death in men with PC and pre-clinical data supporting anti-PC activity, further research on LCDs using long-term PC and CVD end-points is warranted. Funding Sources: Atkins Foundation, American Urological Association, National Institute of Health/National Cancer Institute.